Violating the Fundamental Rights to Life, Liberty and Security of the Person - Jenkin Tsang (McMaster University Library Press, 2020)
In 2015, the Conservative federal government passed Bill C-2, the Respect for Communities Act⏤amending the requirements of applications for exemption from the Canadian Controlled Drugs and Substances Act. These exemptions allowed for supervised consumption sites to legally operate within Canada. The guiding principle behind such services is to promote and protect health through a variety of means, such as: reducing incidence rates of Human Immunodeficiency Virus (HIV), Hepatitis C, and other sexually-transmitted and blood-borne infections; and reducing mortality rates from substance overdose. The reform sought to regulate the exemption application, however, it created an onerous process which made it substantially more difficult to obtain exemptions. The bill was a direct outcome of the ruling of Canada (Attorney General) v. PHS Community Services Society due to the failure by the then Minister of Health, Tony Clement, to grant an extension to Insite, Canada's first legally-exempted supervised consumption site. Within two years, another bill was introduced in an attempt to remove unnecessary barriers created by Bill C-2. As a result of the swift amendments to Bill C-2, there was no formal evaluation conducted to assess the impacts of this reform. Many opponents of Bill C-2 argued that this legislation made it more difficult to develop new or maintain existing supervised consumption sites and as a result violated the rights of the users of these services. En 2015, le gouvernement fédéral a adopté le projet de loi C-2, aussi connu sous le nom de la Loi sur le respect des collectivités. Cette loi modifiait les critères pour la demande d'exemption de la Loi réglementant certaines drogues et autres substances. Cette exemption rendait possible l'opération légale des sites de consommation supervisée, qui visent à réduire les taux de mortalité dus aux surdoses. La réforme avait pour but de réglementer les demandes d'exemption. Or, cette réforme a créé un processus d'application ardu qui a rendu l'accès à ces exemptions considérablement plus difficile. Le projet de loi C-2 est survenu en réaction au verdict qui a été rendu lors du procès Canada (AG) c. PHS. Le refus par le Ministre de la santé, Tony Clement d'accorder une extension à Insite (le premier site de consommation supervisée au Canada) a conduit la Cour suprême à rendre un verdict qui imposait au gouvernement la codification d'un processus d'exemption formel. Deux ans après C-2, un autre projet de loi a été adopté afin de remédier aux barrières inutiles imposées par le projet de loi C-2. En conséquence des modifications rapides au projet de loi C-2, les répercussions de cette réforme n'ont jamais été formellement évaluées. Plusieurs adversaires du projet de loi C-2 soutenaient que cette législation violait les droits des usagers des sites de consommation supervisée car elle rendait la création de nouveaux sites et l'entretien d'anciens sites plus difficiles.